2014
DOI: 10.1103/physrevlett.113.071601
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Thermalization, Stability of Anti–de Sitter Space, and the Fermi-Pasta-Ulam Paradox

Abstract: For a real massless scalar field in general relativity with a negative cosmological constant, we uncover a large class of spherically symmetric initial conditions that are close to anti-de Sitter space (AdS) but whose numerical evolution does not result in black hole formation. According to the AdS/conformal field theory (CFT) dictionary, these bulk solutions are dual to states of a strongly interacting boundary CFT that fail to thermalize at late times. Furthermore, as these states are not stationary, they de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
347
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(369 citation statements)
references
References 19 publications
21
347
0
1
Order By: Relevance
“…It was also observed that half of the naïvely expected channels to transfer energy are actually absent, which leads to extra conserved quantities. This may explain the stable, quasiperiodic solutions which are also often observed during numerical simulations [6,[10][11][12].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…It was also observed that half of the naïvely expected channels to transfer energy are actually absent, which leads to extra conserved quantities. This may explain the stable, quasiperiodic solutions which are also often observed during numerical simulations [6,[10][11][12].…”
Section: Introductionsupporting
confidence: 58%
“…Here we will revisit the proof of those conservation laws and show that they are also valid in the ϕ 4 theory even without spherical symmetry. We first follow the two-time formalism introduced in [10]. Instead of the naïve perturbative expansion in Eq.…”
Section: A Extra Conserved Quantitiesmentioning
confidence: 99%
“…In the context of holography, early indications supported this for generic far-from-equilibrium, arbitrary low-energy states of strongly coupled conformal gauge theories, even when the dynamical evolution of these states was artificially restricted to symmetric submanifolds of the full phase space of the theory 9 [29,30]. Shortly thereafter it was argued [31][32][33] that in fact symmetric phase space of holographic conformal field theories has islands of stability that never equilibrate. In this study we identified yet another possibility: initial states of holographic strongly coupled gauge theories, well described classically in the gravitational frame, evolve to a singularity in finite time.…”
Section: Jhep07(2017)135mentioning
confidence: 99%
“…A priori, E initial and ∆E are independent. However, in our case, we already demanded E initial ∼ ∆E and thus, using dimensional analysis, we can arrive at 28) where α 1,2 are two constants and A denotes the area of the entangling surface.…”
Section: Regimes Of Thermalizationmentioning
confidence: 99%